Group search optimiser: a brief survey. (1st January 2013) - Wei, Changcheng; Fang, Juanyan
Group search optimiser (GSO) is a new swarm methodology algorithm inspired by animal behaviour. In GSO, the total individuals are divided into three kinds: producer, scroungers and rangers. In this paper, we provide a brief survey varying from the member updating strategies, topology and hybridisation. Finally, some future research topics are discussed.